Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/adom.201601028
|View full text |Cite
|
Sign up to set email alerts
|

Compact Generation of Airy Beams with C‐Aperture Metasurface

Abstract: A novel method to launch finite power Airy beams based on a metasurface is presented. By tailoring the amplitude and phase of the transmitted fields from a metallic C‐aperture array, launching Airy beams is achieved in free space. The amplitude and phase of the Airy beam profile can be mapped and tailored by tuning only the tilt angles of the aperture. This structure has multifrequency characteristics, which facilitates Airy beam steering because the trajectory of Airy beams is dependent on the wavelength. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…[164] The bending degree of the generated Airy beam can also be easily controlled by changing the number of nanorods. [165] The nondiffracting Airy beams can also be generated in the terahertz (THz) range and even to be dualwavelength. [165] The nondiffracting Airy beams can also be generated in the terahertz (THz) range and even to be dualwavelength.…”
Section: Other Applications In Beam Manipulation or Controlmentioning
confidence: 99%
“…[164] The bending degree of the generated Airy beam can also be easily controlled by changing the number of nanorods. [165] The nondiffracting Airy beams can also be generated in the terahertz (THz) range and even to be dualwavelength. [165] The nondiffracting Airy beams can also be generated in the terahertz (THz) range and even to be dualwavelength.…”
Section: Other Applications In Beam Manipulation or Controlmentioning
confidence: 99%
“…

the generation of Airy beams, it is highly desirable to locally control the amplitude and phase of the output beam simultaneously so as to satisfy the polynary amplitude and binary phase distributions. [15][16][17] Inspired by the flexibility of introducing complex field distributions, [18] various Airy beam generators, either for free-space light, [19][20][21][22][23][24][25] or surface plasmons, [20,[26][27][28][29][30] have been proposed and demonstrated based on metasurfaces. Recent studies have demonstrated that, manipulating the amplitude and phase simultaneously and independently leads to new wavefront manipulation effects and applications.

…”
mentioning
confidence: 99%
“…[15][16][17] Inspired by the flexibility of introducing complex field distributions, [18] various Airy beam generators, either for free-space light, [19][20][21][22][23][24][25] or surface plasmons, [20,[26][27][28][29][30] have been proposed and demonstrated based on metasurfaces. [19,22,24,25] All these meta-atoms provide us with a robust tool to control the wave front of output beams appreciably across a resonance, and hence can be utilized to generate Airy beams. [23] Typically, wavelength-scale engineered gratings, [26,29] graded nanocavity array, [27,28] and nanoslit resonators [20,30] are widely used to generate plasmonic Airy plasmons.…”
mentioning
confidence: 99%
See 2 more Smart Citations